Air‐sea CO2 fluxes in the near‐shore and intertidal zones influenced by the California Current. Issue 10 (2nd October 2013) - Reimer, Janet J.; Vargas, Rodrigo; Smith, Stephen V.; Lara‐Lara, Ruben; Gaxiola‐Castro, Gilberto; Martín Hernández‐Ayón, J.; Castro, Angel; Escoto‐Rodriguez, Martin; Martínez‐Osuna, Juan
Abstract : [1] The study of air‐sea CO2 fluxes ( F CO2 ) in the coastal region is needed to better understand the processes that influence the direction and magnitude of F CO2 and to constrain the global carbon budget. We implemented a 1 year (January through December 2009) paired study to measure F CO2 in the intertidal zone (the coastline to 1.6 km offshore) and the near‐shore (∼3 km offshore) off the north‐western coast of Baja California (Mexico); a region influenced by year‐round upwelling. F CO2 was determined in the intertidal zone via eddy covariance; while in the near‐shore using mooring buoy sensors then calculated with the bulk method. The near‐shore region was a weak annual net source of CO2 to the atmosphere (0.043 mol CO2 m −2 y −1 ); where 91% of the outgassed F CO2 was contributed during the upwelling season. Sea surface temperature (SST) and Δ p CO2 (from upwelling) showed the strongest relationship with F CO2 in the near‐shore, suggesting the importance of meso‐scale processes (upwelling). F CO2 in the intertidal zone were up to four orders of magnitude higher than F CO2 in the near‐shore. Wind speed showed the strongest relationship with F CO2 in the intertidal zone, suggesting the relevance of micro‐scale processes. Results show that there are substantial spatial and temporal differences in F CO2 between the near‐shore and intertidal zone; likely a result of heterogeneity. We suggest that detailed spatial and temporal measurements are needed across the coastal oceans and continental margins to better understand the mechanisms which control F CO2, as well as reduce uncertainties and constrain regional and global ocean carbon balances. Key Points: Spatial variation influences CO2 flux estimates in coastal regions Different processes control ocean CO2 flux during different seasons/locations